Anisotropy in the Raman scattering of a CaFeO2.5 single crystal and its link with oxygen ordering in Brownmillerite frameworks. (19th May 2015) - Piovano, Andrea; Ceretti, Monica; Johnson, Mark R; Agostini, Giovanni; Paulus, Werner; Lamberti, Carlo
Abstract: Periodic DFT calculations allow an understanding of the strong orientation-dependent Raman spectra of oriented CaFeO2.5 single crystals. Modes involving the oscillation of the apical oxygen (Oap ) atoms perturb the induced electric dipoles. These are formed by anisotropy in the charge distribution and are found to be strongly enhanced when the electric field of the linearly polarized laser line is parallel to the b axis. For the CaFeO2.5 ordered system, strong polarizability of these modes corresponds to strong Raman intensities. Conversely, the apical oxygen disorder observed in low-temperature oxygen-conducting SrFeO2.5 destroys the long-range coherence of the respective Raman modes, which consequently show a strongly reduced intensity. This study provides a vibrational tool to discriminate between ordered and disordered isomorporphous ABO2.5 Brownmillerite frameworks. Furthermore, in combination with DFT calculations, we have found that the weakening of the interlayer interactions is responsible for the loss of ordering in Brownmillerite compounds.